Lac terpene acid-based adhesive as well as preparation method and application thereof
The adhesive A-LTA prepared by cross-linking reaction of shellac terpeneic acid and melamine solves the problems of high-value utilization of shellac waste liquid and the improvement of multifunctional adhesive performance, achieving high adhesion strength and resistance Chemical properties, suitable for a variety of substrates and maintain bonding effect in harsh environments, reduce production costs and provide green economic development direction for lac production enterprises.
Patent Information
- Application Number
- CN202411357343.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The high-value utilization of existing shellac waste liquid has problems such as unclear mechanism, complex process, high cost and material performance that need to be improved. When looking for safe, non-toxic, cheap, and good long-term stability, we encounter multifunctional adhesives. To the challenge.
By crosslinking the refined shellacterpeneic acid and melamine, a novel thermally curable adhesive A-LTA is prepared, suitable for stainless steel, aluminum, tempered glass, wood and bamboo and other substrates, and It exhibits high adhesion strength and stability in harsh environments such as humid, acidic, alkaline, salt, and organic solutions.
It has achieved the preparation of high-value adhesives, which have high adhesion strength, high temperature resistance, mechanical strength and excellent chemical resistance. It can maintain the bonding effect in harsh environments, reduce production costs, and provide shellac manufacturers with The low-carbon development direction of the green economy.
Smart Images

Figure BDA0005063994590000161 
Figure HDA0005063994600000011 
Figure HDA0005063994600000012
Abstract
Description
Technical Field
[0001] The invention relates to an adhesive and a preparation method thereof, in particular to a thermosetting adhesive and a preparation method thereof, and belongs to the technical field of synthetic application of natural products. Background Art
[0002] In order to obtain high-value industrial raw material elaioclase acid compounds, the industry usually adopts the method of saponification and hydrolysis of lac resin. However, a large amount of waste liquid (referred to as lac waste liquid) generated during the production process can only be incinerated or landfilled after treatment as waste. This waste liquid treatment method not only seriously pollutes the environment, but also causes a great waste of resources, and at the same time brings negative effects on the comprehensive benefits of lac processing enterprises. In recent years, low-carbon development has become a new trend for adjusting industrial structure and developing green economy. Therefore, it has become an urgent need for relevant research institutions and enterprises to find suitable utilization methods for lac waste liquid and realize the high-value utilization of lac waste liquid.
[0003] There are many studies on the high-value utilization of lac waste liquid. For example, Tang Hui et al. obtained lac waste residue after drying lac waste liquid, and then developed a variety of materials using lac waste residue. First, the lac waste residue was coupled with polyvinyl alcohol to prepare a reactive composite foam material, which effectively improved the mechanical strength of the original polyethanol foam; the lac waste residue was dehydrated and grafted and coupled with alcoholysed polyester waste, polymerized rosin glycidyl ester, etc. to prepare a hot melt adhesive with low melting point and good fluidity; the lac waste residue was modified to prepare a urea-formaldehyde resin foam material with reduced formaldehyde emission. In addition, there are studies that use lac waste residue glue as a raw material to react with epoxy groups for cross-linking and chain extension to prepare a foam material that can be used for soilless cultivation. Suchandra et al. further acidified and purified the waste liquid after extracting lac eugenol acid, then added maleic anhydride for esterification, and finally mixed it with jute fiber or betel nut fiber to prepare two composite materials with good mechanical strength.
[0004] Although existing studies have provided the possibility of high-value utilization of lac waste liquid, there are still problems such as unclear mechanism, complex process, high cost, and material performance needs to be improved. Therefore, it is still a huge challenge to further explore the high-value utilization of lac waste liquid and develop new materials for sustainable use.
[0005] In the previous work, the researchers found that a large amount of lac terpene acid mixture (Lactose terpene acid, LTA) can be obtained after washing the lac waste liquid. After separation and identification, LTA mainly contains about 70wt% of shell acid (Shellolic acid) and shell acid (Shellolic acid isomer), shell alcohol acid (laksholicacid isomer) and shell alcohol acid (laksholic acid), shell aldehyde acid (Jalaric acid) and shell aldehyde acid (Laccijalaric acid), etc. The chemical structure of each component of LTA contains a large number of hydroxyl groups, carboxyl groups, aldehyde groups and carbon-carbon double bonds, which provide active sites for many chemical reactions, help to generate structurally diverse lac terpene acid derivatives and prepare novel functional materials.
[0006] In recent years, with the rapid development of marine engineering, transportation, construction industry and daily life, there is an increasing demand for multifunctional adhesives such as long-term strong adhesion and underwater adhesion of various materials. Although there are many multifunctional adhesives, from traditional phenolic resins, urea-formaldehyde resins, polyurethane adhesives to modern bionic adhesives, light / thermal adhesives, pressure-sensitive adhesives, etc., it is still a challenge to find safe, non-toxic, cheap and long-term stable adhesives.
[0007] The present invention uses refined LTA as a raw material, prepares a novel heat-curable adhesive A-LTA by reacting with melamine, explores the curing mechanism, and examines its application on substrates such as stainless steel, aluminum, tempered glass, wood and bamboo. The present invention provides a novel solution and theoretical basis for the high-value utilization of shellac waste liquid, and helps shellac production enterprises adjust their industrial structure and develop a low-carbon development of a green economy. Summary of the invention
[0008] The purpose of the present invention is to prepare a thermosetting adhesive, a shellac terpene acid-based adhesive, by high-value utilization of the existing industrial raw material, shellac ketoacid production waste liquid, and the thermosetting adhesive prepared by cross-linking reaction between shellac terpene acid, a product of shellac waste liquid refining treatment, and a cross-linking agent has high adhesion strength, especially strong wet adhesion strength and high stability, and is particularly suitable for use in harsh environments such as humidity, acidity, alkali, salt, and organic solutions.
[0009] To achieve the purpose of the present invention, the present invention provides a method for preparing a shellac terpene acid-based adhesive, which is characterized in that it includes cross-linking shellac terpene acid LTA with a cross-linking agent, wherein the cross-linking agent is melamine, urea, polyethylene glycol, ethylenediamine or triethylenetetramine.
[0010] Wherein, the cross-linking agent is melamine or urea, preferably melamine.
[0011] Particularly, the mass ratio of melamine to LTA is (8-23):100, preferably 23:100.
[0012] Particularly, the temperature of the cross-linking reaction is 55-85°C, preferably 65-75°C, and more preferably 70°C; the cross-linking reaction time is 0.5-1.5h, and preferably 1h.
[0013] Another aspect of the present invention provides a method for preparing a shellac terpene acid-based adhesive, comprising the following steps in order:
[0014] 1) dissolving shellac terpene acid LTA in sodium hydroxide solution to prepare LTA-sodium hydroxide solution;
[0015] 2) adding melamine to the LTA-sodium hydroxide solution to carry out a cross-linking reaction;
[0016] 3) adding formic acid as a pH additive to the cross-linking reaction mixture to adjust the pH of the reaction mixture, and stirring the reaction mixture for at least 30 minutes while maintaining the pH value of the reaction mixture at 3-5;
[0017] 4) After stirring, the reaction solution is cooled to room temperature and allowed to stand for stratification, the upper clear liquid is discarded, and the lower viscous material is washed with water until it becomes neutral, thereby obtaining a shellac terpene acid-based adhesive.
[0018] Wherein, the lac terpene acid LTA in step 1) is prepared according to the following method:
[0019] 1A) adding the shellac waste liquid into a sulfuric acid solution, stirring and mixing, and performing an acid precipitation precipitation treatment;
[0020] 1B) After the acid precipitation treatment for at least 25 minutes, the upper solution was removed, and then water was added to the precipitate produced by the acid precipitation, and the precipitate was stirred and washed 4-6 times;
[0021] 1C) The washed precipitate is freeze-dried and vacuum-dried in sequence to obtain the purified shellac terpene acid raw material LTA.
[0022] Wherein, the lac waste liquid in step 1A) is the waste liquid after elaeis acid is extracted from lac resin (referred to as lac waste liquid for short).
[0023] Particularly, the mass percentage concentration of the sulfuric acid solution is 15-20%, preferably 18%.
[0024] Particularly, the pH of the shellac waste liquid is adjusted to 3.0±0.2 by adding sulfuric acid solution.
[0025] In particular, ultrasonic treatment is used for the stirring and mixing, wherein the temperature of the acid precipitation treatment is controlled to be 35±2°C during the ultrasonic stirring process; the ultrasonic stirring rate is 40-60rpm (preferably 50rpm); the ultrasonic power is 53±3KHz; and the ultrasonic stirring time is 25-40min, preferably 25-35min, and more preferably 30min.
[0026] In particular, the time for washing the precipitation with water in step 1B) is 15-30 min, preferably 20 min.
[0027] In particular, the process control conditions of freeze-drying in step 1C) are: freezing temperature -52±2°C, vacuum degree 0.03±0.01 mbar (3 Pa), and freezing time 48±5h.
[0028] In particular, the process conditions of vacuum drying in step 1C) are: temperature of 60° C. (usually 55-65° C.); drying time of 48 h (usually 40-55 h); relative vacuum degree of -0.0095 MPa (usually lower than 0 MPa, preferably -0.05 to -0.1 MPa);
[0029] The water content of the shellac terpene acid raw material obtained by drying is less than 1.0%, preferably 0.1-1.0%, and more preferably 0.15%.
[0030] In particular, the ratio of the mass of LTA to the volume of the sodium hydroxide solution in step 1) is 1:(1-15) g / ml, preferably 1:10 (g / ml), that is, 1 g of LTA is dissolved in 5-15 ml of the sodium hydroxide solution.
[0031] Particularly, the concentration of the sodium hydroxide solution is 0.3-1.0M, preferably 0.5M.
[0032] In particular, the mass ratio of melamine to LTA in the LTA-sodium hydroxide solution in step 2) is (8-23):100, preferably 23:100.
[0033] Particularly, the temperature of the cross-linking reaction is 55-85° C., preferably 65-75° C., and more preferably 70° C.; the cross-linking reaction time is 0.5-1.5 h, and preferably 1 h.
[0034] In particular, the pH adjuster in step 3) is formic acid, acetic acid, or propionic acid, preferably formic acid.
[0035] In particular, the stirring treatment time in step 3) is 30-60 min, preferably 40 min.
[0036] Particularly, formic acid is added to adjust and maintain the pH value of the reaction mixture to 4.5, and the reaction mixture is stirred for 30-60 minutes, more preferably for 40 minutes.
[0037] Particularly, the stirring process rate is 200±50 rpm; and the stirring temperature is 60±2°C.
[0038] Another aspect of the present invention provides a shellac terpene acid-based adhesive prepared according to the above method.
[0039] In another aspect, the present invention provides an application of a shellac terpene acid-based adhesive, wherein the shellac terpene acid-based adhesive is applied to a substrate to be bonded, and then subjected to a heat curing treatment, wherein the heat curing treatment temperature is 200-250° C. and the heat curing time is at least 3 minutes; or the shellac terpene acid-based adhesive is heated to ≥67° C., melted, and then coated on the substrate to be bonded, and then bonded into one after cooling.
[0040] In particular, the heat curing treatment temperature is 200-250° C., preferably 215-250° C., and more preferably 245° C.; the heat curing time is 3-10 min, and preferably 4 min.
[0041] In particular, the shellac terpene acid-based adhesive is heated to 67° C.-245° C. to melt the adhesive, and after the adhesive is melted for at least 10 minutes (usually 10-30 minutes), it is applied to the substrate to be bonded.
[0042] In this paper, a novel heat-curable adhesive A-LTA was prepared by reacting refined shellac terpene acid with melamine. Thanks to the fact that the adhesive A-LTA contains multiple functional groups such as amide, imine, and ester, it can be cross-linked and polymerized under high temperature conditions to form a network structure with multiple chemical bonds and a dense structure. Therefore, the prepared adhesive A-LTA has high bonding strength and bending strength for substrates such as stainless steel, aluminum, tempered glass, dragon bamboo, and poplar in a wide temperature range. Its performance is better than most commercially available adhesives, showing the potential for general bonding applications on various substrate surfaces. At the same time, the stability test results show that the adhesive A-LTA can maintain a strong and effective bonding effect after being immersed in strong acid, strong alkali, water, and organic solvents for 7 days, and can resist harsh external environments. It has significant advantages in industrial production and environmental protection, and therefore has great application potential as a multifunctional adhesive. The present invention provides a novel solution and theoretical basis for the high-value utilization of shellac waste liquid, which is helpful for shellac production enterprises to adjust their industrial structure and develop low-carbon development of green economy.
[0043] Compared with the prior art, the present invention has the following advantages and benefits:
[0044] 1. The adhesive of the present invention uses shellac waste liquid as a raw material to prepare a high-value adhesive, thereby saving resources and avoiding environmental pollution; a new and suitable utilization path is found for the development and utilization of shellac waste liquid, and a new method is provided for the high-value utilization of shellac waste liquid.
[0045] 2. The shellac terpene acid-based adhesive A-LTA of the present invention can withstand higher temperatures after curing and will not soften at high temperatures like thermoplastic adhesives. It has high high temperature resistance and can withstand temperatures as high as 245°C.
[0046] 3. The shellac terpene acid-based adhesive A-LTA of the present invention has good mechanical strength. After thermal curing, A-LTA has high hardness and strength, can withstand large mechanical loads, and the bending strength of the bonding stainless steel substrate reaches more than 139 MPa;
[0047] 4. The shellac terpene acid-based adhesive A-LTA of the present invention has excellent chemical resistance and can withstand harsh external environments. After thermal curing, A-LTA has good resistance to various chemical substances such as acids, alkalis, salts, and organic solvents. The adhesive of the present invention has high stability when used in a chemical environment and can maintain a strong and effective bonding effect after being immersed in strong acids, strong alkalis, water, and organic solvents for 7 days.
[0048] 5. The shellac terpene acid-based adhesive A-LTA prepared by the method of the present invention has a wide range of applications. The adhesive A-LTA can be used to bond a variety of materials, including metal, glass, plastic, wood, and composite materials.
[0049] 6. The shellac terpene acid-based adhesive A-LTA prepared by the method of the present invention has strong stability, and the chemical structure of the adhesive A-LTA after thermal curing is very stable, so its bonding performance can be maintained for a long time.
[0050] 7. The preparation method of the shellac terpene acid-based adhesive of the present invention is simple, the preparation process steps are short, the process conditions are mild and easy to control, and it is suitable for large-scale promotion and application, and reduces the production cost of thermosetting adhesives.
[0051] The shellac terpene acid-based adhesive A-LTA prepared by the method of the invention is a new type of adhesive independently developed, which realizes the high-value utilization of shellac waste liquid and creates a new research direction for shellac terpene acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The effect of formic acid dosage on the pH of the cross-linking reaction solution and the adhesion performance of the adhesive; wherein A) is the effect on the pH of the cross-linking reaction solution, and B) is the effect on the shear strength;
[0053] Figure 2 The effect of stirring time on adhesion properties after adding formic acid for the cross-linking reaction;
[0054] Figure 3 The effect of cross-linking reaction temperature on the adhesion performance of adhesive;
[0055] Figure 4 The effect of the amount of cross-linking agent used in the cross-linking reaction on the adhesion performance of the adhesive;
[0056] Figure 5 : Infrared spectra of raw material LTA, adhesive A-LTA, and cured product. In the figure, 105, 150, and 245°C respectively represent the product after the adhesive is thermally cured at 105, 150, and 245°C;
[0057] Figure 6 X-ray photoelectron spectroscopy test for adhesive A-LTA;
[0058] Figure 7 DSC, TG and DTG curves of LTA, melamine and adhesive A-LTA; wherein: A) is a DSC curve; B) is a TG and DTG curve of adhesive A-LTA;
[0059] Figure 8 A is the test graph of viscosity variation of adhesive A-LTA with temperature;
[0060] Figure 8 B is the test graph of the modulus of adhesive A-LTA changing with temperature;
[0061] Figure 8 C is the change of modulus of the cured product of adhesive A-LTA over time at room temperature;
[0062] Fig. 9 The adhesive properties of the adhesive prepared by the present invention after heat curing at different temperatures;
[0063] Fig.10 The adhesion performance of the adhesive at different curing times;
[0064] Fig.11 The results of the adhesive A-LTA adhesion test on different substrates are shown below;
[0065] Fig.12 These are bending strength test graphs of adhesives bonded to different substrates, wherein A) is a bending strength test graph of the A-LTA adhesive of the present invention bonded to different substrates; B) is a bending strength test graph of the A-LTA adhesive and commercially available adhesive bonded to a stainless steel substrate.
[0066] Fig.13 This is a test diagram of the wet adhesion performance of adhesive A-LTA after being immersed in different solutions. DETAILED DESCRIPTION
[0067] The present invention will be further described below in conjunction with specific embodiments, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are exemplary only and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.
[0068] Raw materials, reagents and instruments
[0069] Sodium hydroxide, sodium chloride, petroleum ether (boiling range 60-90°C) and formic acid were purchased from Guangdong Guanghua Technology Co., Ltd.; melamine was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; shellac waste liquid (solid matter is 76.9wt%) was derived from Mojiang Senyuan Technology Co., Ltd.; all the water used in the experiment was deionized water; Product 1 is metal welding glue, Product 2 is epoxy resin structural glue, and Product 3 is Shuangyi all-purpose glue.
[0070] DF-101S collector constant temperature heating magnetic stirrer Changzhou Aohua Instrument Co., Ltd.; VOS-310C vacuum constant temperature dryer Shanghai Airo Instrument Co., Ltd.; FD-1C-50 freeze dryer Beijing Boyikang Experimental Instrument Co., Ltd.; AGX-V-5KN universal testing machine Shimadzu Corporation; DTD-6 digital display constant temperature digester Changzhou Jintan Liangyou Instrument Co., Ltd.; SRJX-4-9 muffle furnace Jinsha Electric Furnace Factory, Nantong County, Jiangsu Province; DISCOVERY HR-2 rheometer TA Company, USA; electronic balance Sartorius Scientific Instrument (Beijing) Co., Ltd.; ultrasonic cleaner (SK8210HP) Shanghai Kedao Ultrasonic Instrument Co., Ltd.; moisture analyzer (HX204) Mettler-Toledo, Switzerland; Tensor-27 Fourier transform infrared spectrometer Netzsch, Germany; FiveEasy Plus pH meter Mettler-Toledo Instrument (Shanghai) Co., Ltd.
[0071] Example 1 Refining treatment of spent shellac acid (preparation of raw shellac terpene acid LTA)
[0072] 1. Acid precipitation treatment
[0073] 200.0 g of shellac waste liquid is put into a 2.0 L beaker, 1000 mL of sulfuric acid solution (mass percentage concentration is 18%, usually 15-20%) is added to adjust the pH of the shellac waste liquid to 3.0 (usually 3.0±0.2), and the shellac waste liquid is placed in an ultrasonic cleaning instrument for ultrasonic stirring to obtain acid precipitation, wherein the ultrasonic stirring rate is controlled to be 50 rpm (usually 40-60 rpm); the ultrasonic power is 53±3 KHz; and the stirring temperature is 35±2° C.;
[0074] 2. Washing
[0075] Ultrasonic stirring, acid precipitation treatment for 30 minutes (usually 25-40 minutes, preferably 25-35 minutes), then pour out all the sulfuric acid solution; add 0.8L of water to the acid precipitation and wash it with ultrasonic stirring for 5 times (usually 4-6 times) to remove a large amount of water-soluble impurities, each ultrasonic stirring washing time is 20 minutes (usually 15-30 minutes), after each ultrasonic stirring, let it stand for 10 minutes (usually 7-15 minutes), and then pour out the upper liquid to obtain a washed precipitate;
[0076] 3. Drying
[0077] The washed precipitate is freeze-dried and vacuum-dried in sequence to obtain a refined shellac terpene acid raw material (LTA), wherein:
[0078] The process control conditions of freeze drying are: freezing temperature -52±2℃, vacuum degree 0.03mbar (3pa), freezing time 48h±2. The process conditions of vacuum drying are: temperature 60℃ (usually 55-65℃); drying time 48h (usually 40-55h); relative vacuum degree -0.0095MPa (usually lower than 0MPa, preferably -0.05~-0.1MPa);
[0079] The moisture content of the shellac terpene acid LTA raw material obtained by drying is 0.15% (usually lower than 1.0%, preferably 0.1-1.0%).
[0080] The shellac terpene acid raw material was stored in a refrigerator at -20°C. When used, the water content of LTA was controlled to be less than 0.15%.
[0081] The adhesion strength of thermosetting cross-linking after direct solvent-free mixing of LTA and melamine is low, and LTA is only soluble in alkaline solutions but not in neutral or acidic solutions. Therefore, LTA is first dissolved in an alkaline solution and reacted with melamine, and then formic acid is added to adjust the pH value of the solution, thereby precipitating a prepolymer to obtain higher adhesion strength.
[0082] Example 2A Screening of cross-linking agents
[0083] 1. Preparation of adhesive
[0084] Weigh LTA (1.0 g) prepared according to the method of Example 1 and dissolve it in 10.0 mL of sodium hydroxide solution (concentration is 0.5 mol / L, usually 0.3-1.0 M) to prepare LTA-sodium hydroxide solution;
[0085] In this embodiment, the ratio of the mass of LTA in the LTA-sodium hydroxide solution to the volume of the sodium hydroxide solution is described by taking 1:10 (g / ml) as an example, and other mass-volume ratios such as 1:(1-15) g / ml are also applicable to the present invention.
[0086] Then, 0.08 g of cross-linking agent (urea, melamine, polyethylene glycol, ethylenediamine, triethylenetetramine) was weighed and added to different LTA-sodium hydroxide solutions, and then the cross-linking reaction was carried out at 60°C for 1 h.
[0087] Then, 0.3 mL of formic acid was added to the cross-linking reaction solution to adjust the pH value of the solution to 4.5;
[0088] Then, the cross-linking reaction mixture was stirred for another 40 min at a pH of 4.5;
[0089] After the reaction was completed, the reaction solution was cooled to room temperature and the supernatant was poured off. The lower viscous material was taken out and washed with water until the outflowing solution was neutral, thereby obtaining the adhesive A-LTA.
[0090] 2. Determination of dry adhesion strength
[0091] The dry adhesion strength of the prepared adhesive was measured according to the national standard GB / T7124-2008 ("Determination of tensile shear strength of adhesives (rigid material to rigid material)"), wherein the dry adhesion strength measurement method is as follows:
[0092] Apply glue on one side of two stainless steel substrates, with a length of 12.5 mm, a width of 25 mm, and a thickness of 0.1 mm. After the glue is applied, bond the two stainless steels in the glued area and apply a unit area (mm 2 ) is a pressure of 1.38MPa. After applying pressure for 1 minute, the bonded substrates are placed in an oven, heated and heat-cured while maintaining the temperature at 185°C. After heat curing for a period of time, the substrates are taken out and cooled to room temperature. The adhesion shear strength is then tested on a universal testing machine to evaluate the adhesion strength. During the test, the fixture spacing is set to 90mm, the test speed is 10mm / min, the heat curing temperature is 185°C, and the curing time is 3min.
[0093] The measurement results show that when cross-linking agents ethylenediamine or triethylenetetramine are added to LTA, the prepared mixed system remains in a liquid state under high temperature conditions and cannot form a viscous polymer; the adhesive formed after adding polyethylene glycol, urea and melamine has adhesion strengths of 2.27MPa, 3.23MPa and 3.86MPa on stainless steel respectively.
[0094] Therefore, melamine with the highest adhesion strength was selected as the cross-linking agent to further optimize the process conditions for preparing an adhesive with greater adhesion strength and better stability.
[0095] Example 2B Cross-linking reaction pH screening
[0096] The adhesive was prepared by the same method as in Example 2A, except that the amount of cross-linking agent melamine was 0.08 g; the amounts of formic acid were 0.1, 0.2, 0.3, 0.4, and 0.5 ml, respectively, and the corresponding solution pH values were 6.5, 5.0, 4.5, 3.5, and 3.0, respectively.
[0097] The results of the test are as follows Figure 1 Adding too much or too little formic acid will reduce the adhesion strength. When 0.3 mL of formic acid is added, the pH value of the precipitated solution can be adjusted to about 4.5, at which time the precipitated adhesive has the highest adhesion strength. Therefore: the amount of formic acid is 0.2-0.5 ml, preferably 0.3 ml; the solution pH is 3.0-5.0, preferably 4.5.
[0098] Example 2C Screening of stirring time after cross-linking reaction
[0099] The method is the same as Example 2A except that the amount of the cross-linking agent melamine used is 0.08 g; and after the formic acid is added, the stirring time for the cross-linking reaction mixture is continued for 20, 30, 40, 50, and 60 minutes, respectively.
[0100] The results of the test are as follows Figure 2 The main purpose of adding formic acid is to adjust the pH value of the solution so that the adhesive can precipitate. Figure 2 It can be seen that the adhesion strength increases first and then remains basically unchanged with the stirring time. In order to obtain the highest adhesion strength, the stirring time should be controlled to about 40 minutes, usually 30-60 minutes.
[0101] Example 2D Cross-linking reaction temperature screening
[0102] Except that the amount of cross-linking agent melamine used is 0.08 g and the cross-linking reaction temperatures are 25, 40, 55, 70, and 85° C., the rest is the same as Example 2A.
[0103] The results of the test are as follows Figure 3 As shown. In the reaction temperature range of 25℃ to 55℃, the adhesive strength of the obtained adhesive increases slightly with the increase of temperature; the highest adhesive strength can be obtained when the temperature rises to 70℃; when the temperature continues to rise to 85℃, the adhesive strength of the adhesive has no obvious change compared with 70℃. Therefore, the optimal reaction temperature is preferably 70℃ (usually 70±5℃).
[0104] Example 2E Screening of cross-linking agent dosage
[0105] Except that the masses of the cross-linking agent melamine are 0, 0.03, 0.08, 0.13, 0.18, 0.23, 0.28 and 0.3 g respectively, the rest are the same as Example 2A.
[0106] The results of the test are as follows Figure 4 As shown. Without adding the crosslinking agent melamine, only LTA was used as the raw material for heat curing and crosslinking under the same conditions, and the measured adhesion strength was only 1.25MPa; as the addition amount of melamine gradually increased from 3.0% to 33.0% (the percentage of melamine in the raw material of shellac terpene acid), the adhesion strength of the obtained adhesive increased first and then decreased. When the addition amount of the crosslinking agent was 23.0% of the mass of the raw material LTA, the adhesive adhesion strength was the largest. After exceeding 23%, the strength gradually decreased. Therefore, the amount of the crosslinking agent was selected to be 8-23% (0.08-0.23g).
[0107] The optimal preparation process of A-LTA was determined by the above single factor experiments (Examples 2A-2E): 1.0 g LTA was weighed and dissolved in 10.0 mL of 0.5 mol / L -1 Then, 0.23g of melamine crosslinking agent was added to the reaction solution for crosslinking reaction at 70°C for 1h, 0.3mL of formic acid was added to the reaction solution to adjust the pH value of the solution to 4.5, and then the mixture was stirred for 40min. After the reaction was completed, the reaction solution was cooled to room temperature and the upper clear liquid was poured off, and the lower viscous material was taken out and washed with water until the solution was neutral. The obtained substance was the adhesive A-LTA.
[0108] Example 3 Preparation of Adhesive
[0109] Weigh LTA (1.0 g) prepared according to the method of Example 1 and dissolve it in 10.0 mL of sodium hydroxide solution (concentration is 0.5 mol / L, usually 0.3-1.0 M) to prepare LTA-sodium hydroxide solution for later use;
[0110] Then, 0.23 g of melamine crosslinking agent was added, and the crosslinking reaction was carried out at 70° C. (usually 55-85° C.) for 1 h (usually 0.5-1.5 h);
[0111] Then, 0.3 mL of formic acid is added to the cross-linking reaction solution to adjust the pH value of the solution to 4.5 (usually 4.5±0.2); then, the cross-linking reaction mixture is stirred for 40 min (usually 30-60 min) at a pH value of 4.5; the stirring rate is 200 rpm (usually 150-250 rpm); and the stirring temperature is 60±2° C.;
[0112] After the reaction is completed, the reaction solution is cooled to room temperature and the upper clear liquid is poured off, and the lower viscous material is taken out and washed with water until the outflowing solution is neutral, thereby obtaining the adhesive A-LTA of the present invention.
[0113] Example 4 Heat curing of adhesive
[0114] The dry adhesion properties of the prepared adhesive were measured according to the national standard GB / T 7124-2008 ("Determination of tensile shear strength of adhesives (rigid material to rigid material)").
[0115] Apply glue on one side of two stainless steel substrates, with a length of 12.5 mm, a width of 25 mm, and a thickness of 0.1 mm. After the glue is applied, bond the two stainless steels in the glued area and apply a unit area (mm 2 ) is 1.38MPa, and after applying pressure for 1min, the adhesive stainless steel substrate is obtained and set aside;
[0116] The different adhesive stainless steel substrates after bonding were placed in ovens at different temperatures for heat curing treatment. After a period of heat curing treatment, they were taken out and cooled to room temperature. Then, the adhesion shear strength was tested on a universal testing machine to evaluate the adhesion strength. During the test, the fixture spacing was set to 90mm and the test speed was 10mm / min. The heat curing treatment temperatures were maintained at 105, 155, 185, 200, 215, 230, and 245℃, respectively, and the curing time was 3min. Five specimens were tested in parallel in each group. The test results are shown in the figure. Fig. 9 .
[0117] Depend on Fig. 9 It can be seen that: under the same heat curing time, the heat curing temperature has a significant effect on the adhesion strength and adhesion performance. When the temperature is lower than 185°C, the adhesion strength of A-LTA has significant differences between different temperatures, while when the heat curing temperature is in the range of 215-245°C, there is no significant difference in its adhesion strength. Therefore, it is more appropriate to select the heat curing temperature of A-LTA to be 245°C, and the heat curing temperature of the adhesive of the present invention is selected to be 200-245°C, preferably 215-245°C.
[0118] Example 5 Heat curing of adhesive
[0119] Apply glue on one side of two stainless steel substrates, with a length of 12.5 mm, a width of 25 mm, and a thickness of 0.1 mm. After the glue is applied, bond the two stainless steels in the glued area and apply a unit area (mm 2 ) is 1.38MPa, and after applying pressure for 1min, the adhesive stainless steel substrate is obtained and set aside;
[0120] The bonded stainless steel substrates were placed in a muffle furnace, heated to 245°C, and then the timing was started. The heating was turned off after heat curing for 0, 2, 3, 4, 5, 6, 8, and 10 minutes. After they were naturally cooled to room temperature, no more pressure was applied, and the stainless steel substrates were taken out to test their adhesion strength.
[0121] The test results are as follows Fig.10 As shown in the figure, heat curing time is an important factor affecting the adhesion strength. When the heat curing time is short, the cross-linking polymerization reaction of A-LTA is incomplete, and its cross-linking structure is less, so the adhesion strength is low; appropriately extending the heat curing time helps A-LTA to cross-link to form a three-dimensional network or body structure, thereby improving its adhesion strength. Therefore, it is more appropriate to select a heat curing time of 3-6 minutes, preferably 4-6 minutes, and more preferably 4 minutes.
[0122] Test Example 1 Infrared Spectroscopy Test
[0123] The functional group of the samples (i.e., the raw material LTA prepared in Example 1, the adhesive A-LTA prepared in Example 3, and the cured product prepared from the adhesive prepared in Example 3) was tested by potassium bromide tablet method using Tensor-27 Fourier transform infrared spectrometer (Netzsch, Germany). The scanning wave number was set to 400-4000 cm -1 , the test results are as follows Figure 5 The solidified product was obtained as follows: 5 g of A-LTA prepared in Example 3 was placed in a glass culture dish, heated to 105, 150, and 245 in a muffle furnace, and the temperature was turned off after solidification for 10 min. After naturally cooling to room temperature, the solidified product was taken out and ground into powder.
[0124] Raw material LTA at 3430cm -1 ,2933 / 2856cm -1 ,1709 / 1250cm -1 ,1636cm -1 The absorption peaks at 3350 / 3150cm correspond to the stretching vibrations of hydroxyl (-OH), methyl and methylene CH, carboxyl -C=O and -CO, and -C=C, while the primary amine group (-NH2) in melamine is at 3350 / 3150cm -1 There are characteristic double absorption peaks.
[0125] The adhesive A-LTA prepared according to the method of the present invention is not a simple superposition of two raw materials. Compared with the raw materials, its -1 The characteristic vibration absorption peaks of -C=N and -CN are increased, and the -NH absorption peak of the primary amino group is weakened.
[0126] When A-LTA was cross-linked and cured at 105°C for 10 min, the obtained cured product had a peak at 1636 cm -1 The absorption peak of -C=C disappears at 1171cm -1 A new stretching vibration absorption peak of -CC was generated at 1734 cm-1, which may be due to the polymerization of carbon-carbon double bonds. When A-LTA was cross-linked and cured at 150 °C for 10 min, the obtained cured product had a peak at 1734 cm-1. -1 A new absorption peak was generated at 1614 / 1457cm, which may be due to the oxidation of the hydroxyl group of A-LTA to aldehyde or ketone carbonyl under high temperature conditions; when A-LTA was cross-linked and cured at 245℃ for 10min, the obtained cured product had a peak at 1614 / 1457cm -1 New absorption peaks of -C=O and -CN were generated at 1734 cm -1 The absorption peaks of aldehyde or ketone carbonyl at 3350 / 3150cm -1 The -NH absorption peak at 245°C disappeared, which may be due to the dehydration of ammonium salt to form amide and the dehydration condensation of carboxyl and amino groups at high temperature; this shows that A-LTA generates an adhesive with a highly cross-linked network structure at 245°C.
[0127] Shellac terpene acid and melamine react in the presence of formic acid (pH=4.5 or so), and the carboxyl group reacts with the amino group to form ammonium salt; DSC and TG show that after exceeding 245°C, the A-LTA adhesive begins to thermally decompose, and its bonding strength decreases. The higher the temperature, the better the performance of the thermosetting adhesive, and the more thorough the polymerization. After rising to 245°C, its bonding strength tends to be stable, and further increasing the temperature will not increase its bonding strength.
[0128] Test Example 2: X-ray Photoelectron Spectroscopy Test
[0129] Under the working conditions of 15 kV and 50 W, the surface elements of the sample (adhesive prepared in Example 3) were measured using a PHI5000 Versaprobe II X-ray photoelectron spectrometer (Japan). The test results are shown in Figure 6 AD, where A is the XPS spectrum of adhesive A-LTA; B is the high-resolution XPS spectrum of C1s; C is the high-resolution XPS spectrum of N1s; and D is the high-resolution XPS spectrum of O1s.
[0130] XPS testing was used to further verify the surface chemical structure of the adhesive, such as Figure 6 As shown in Figure A, the peaks of A-LTA at 283.7eV, 398.2eV and 530.1eV correspond to the three elements C1s, N 1s and O1s, and their corresponding percentages are 65.76%, 23.18% and 11.06%, respectively. Figure 6As shown in Figure B, the C1s spectrum of A-LTA can be divided into four peaks, 284.80 eV corresponds to the C=C / C–C group, 286.09 eV corresponds to the CN / CO group, 287.76 eV corresponds to the C=O / N=CN group and 289.09 eV corresponds to the OC=O group. Figure 6 As shown in Figure C, the N 1s spectrum shows two peaks centered at 398.65 and 399.68 eV, which are attributed to -N=C and CN. Figure 6 The O1s spectrum shown in D shows the presence of C=O (532.20 eV) and CO (533.49 eV). It can be seen that the main functional group structure of A-LTA identified by XPS is consistent with the FTIR result, indicating that the adhesive A-LTA structure contains multiple functional groups such as amide, imine, and ester.
[0131] Experimental Example 3 Differential Scanning Calorimetry (DSC) Test
[0132] 10.0 mg of each of the raw material melamine, the LTA raw material prepared in Example 1, and the adhesive prepared in Example 3 were accurately weighed in an aluminum crucible and placed in a thermogravimeter (STA2500, NETZSCH Scientific Instruments, Germany) respectively. The test atmosphere was high-purity nitrogen, and the gas flow rates of the protective gas and the purge gas were 50 mL.min. -1 and 80mL.min -1 The cooling medium is liquid nitrogen; the heating rate during the test is 10℃.min -1 , DSC analysis was performed at a test temperature of -30 to 300°C. The analysis results are as follows Figure 7 .
[0133] Curing performance and thermal stability are important factors in evaluating adhesives, and play an important role in indicating the use of adhesives and the selection of substrates. The curing process of the adhesive was analyzed by DSC. The results are as follows: Figure 7 As shown in A, melamine itself is a relatively stable material raw material, and it starts to melt when heated above 280°C; the raw material LTA is a multifunctional tricyclic sesquiterpene with a rigid structure, which exhibits a unique glass transition and self-crosslinking curing phenomenon in a wide temperature range of 0 to 275°C. Figure 7 It can be seen that A-LTA is not a simple superposition of LTA and melamine. It has two peaks at 169°C and 215°C, respectively, indicating that A-LTA undergoes two important chemical cross-linking reactions during the heating process and solidifies. Furthermore, the thermal stability of A-LTA was tested using a thermogravimetric analyzer. The results are as follows: Figure 7As shown in Figure B, when the temperature reaches 268°C, the residual mass of the adhesive is still maintained at about 90.0wt%, indicating that the A-LTA has good thermal stability, which is due to the multiple chemical bonds and dense network structure in the cured product playing a thermal stabilizing role.
[0134] Test Example 4 Rheological Test
[0135] A flat plate mold was selected and the adhesive A-LTA (0.8 g) prepared in Example 3 was accurately weighed, and the rheological behavior of the prepolymer was measured on a TA DISCOVERY HR-2 rheometer (TA Company, USA). The Flow Temperature Ramp mode was selected to test the change of viscosity with temperature. The stabilization time before the test was 2 min, the test temperature was 25-300 ° C, and the heating rate was 5.0 ° C. min -1 , the shear rate is 10.0 1.s -1 Select Oscillation Temperature Ramp mode to test the change of storage modulus and energy modulus with temperature, the stabilization time is 2min, the test temperature is 25~300℃, and the heating rate is 5.0℃.min -1 , stress is 8.5Pa, angular frequency is 10rad.s -1 . The Oscillation Time mode was selected to test the changes of the storage modulus and dissipation modulus of the cured product over time at a certain temperature. The stabilization time was 2 minutes, the test time was 150 seconds, the strain was 0.1%, and the frequency was 1.0 Hz. Among them, the tested cured product was prepared according to the following method: the adhesive A-LTA (3 g) prepared according to the method of Example 3 was placed in a glass culture dish, placed in a muffle furnace for heating, and subjected to heat curing treatment at a temperature of 245°C and a time of 4 minutes. The cured product was taken out, cooled to room temperature, and ground into powder; then an appropriate amount of sample was taken and pressed into a circle with a diameter of 2 cm and a thickness of 2 mm, and placed in the center of a flat mold to test the storage modulus and dissipation modulus of the cured product.
[0136] Rheological testing provides an in-depth look into the curing process of adhesives. First, a temperature ramp test was used to investigate the temperature-viscosity relationship. Figure 8 A. Temperature has a great influence on the viscosity of A-LTA. The viscosity first decreases, then increases, and then remains unchanged during the heating process. At room temperature, the initial viscosity of A-LTA is about 2.6×10 3 Pa.s, as the temperature increases, its viscosity decreases rapidly and reaches the lowest point at around 215℃; then as the temperature increases, the viscosity increases sharply and remains at around 2.5Pa.s after the temperature reaches 245℃.
[0137] The temperature-modulus relationship was investigated using the temperature rise test mode. The results are as follows: Figure 8 B. The law of modulus change with temperature is basically consistent with the law of viscosity change. When the temperature rises from 25℃ to 225℃, the energy loss modulus of A-LTA is always greater than the storage modulus, indicating that A-LTA is in a fluid state and mainly undergoes viscous deformation; when the temperature is higher than 225℃, the storage modulus gradually exceeds the energy loss modulus, indicating that A-LTA undergoes cross-linking polymerization and curing reaction.
[0138] The cured product was tested for modulus-time at room temperature. Figure 8 C shows that the storage modulus of the cured product is 1.4×10 5 Pa is significantly greater than the loss modulus, indicating that the cured product is in a stable solid state.
[0139] Test Example 5 Dry Adhesion Strength Test of Different Substrates
[0140] Aluminum sheet, stainless steel sheet, tempered glass, bamboo sheet and poplar wood sheet were selected as the adhesive substrates for investigation. Before adhesion, the metal sheet needs to be polished with sandpaper for 1 minute, and the surface of other substrates should be kept clean before use.
[0141] According to the national standard GB / T 7124-2008 method, single-sided glue (length 12.5mm, width 25mm, thickness 0.1mm) was applied on stainless steel, aluminum, tempered glass and other substrates. After the glue application, the two substrates in the glued area were bonded together, and a pressure of 1.38MPa per unit area was applied to the substrates in the glued area. After applying pressure for 1min, the bonded substrates were placed in a muffle furnace at different temperatures for heat curing for a period of time, then taken out and cooled to room temperature, and then the adhesion shear strength was tested on a universal testing machine to evaluate the adhesion strength. During the test, the fixture spacing was set to 90mm and the test speed was 10mm.min -1 For substrates such as stainless steel, aluminum, and tempered glass, the adhesion strength is tested according to the dry adhesion strength method, with a curing temperature of 245°C and 4 minutes. The adhesion strength is tested after the substrate cools to room temperature.
[0142] The gluing method for dragon bamboo and poplar is as follows: heat the A-LTA prepared according to the method of Example 3 to 190°C, and then apply the glue on the surface of dragon bamboo and poplar for 20 minutes, with the application area of 12.5mm×25mm×0.1mm. Bond two pieces of glued dragon bamboo and poplar, and test the dry adhesion strength after cooling.
[0143] The test results are as follows Fig.11 As shown:
[0144] A-LTA adhesive has good bonding strength on different substrates such as aluminum, stainless steel, tempered glass, bamboo, and poplar, and its bonding strength can reach 11.15MPa, 10.16MPa, 7.78MPa, 2.86MPa, and 2.71MPa ( Fig.11 ). It can be seen that A-LTA can be selectively used for bonding different substrates, among which A-LTA has better bonding effect on metal substrates than other substrates. The optimal curing temperature of the adhesive for metal bonding is 245℃ and the time is 4 minutes, while the bonding temperature of wood and bamboo is 190℃ and the time is 20 minutes. Secondly, at the same temperature, the bonding effect of A-LTA on metal is better than that on glass substrates. This may be because metal substrates have richer pore structures than glass, which can form better mechanical inlays. At the same time, the metal coordination / chelation between A-LTA and the metal surface will also enhance the bonding effect.
[0145] Test Example 6 Bending Strength Test of Different Substrates
[0146] Referring to the test method of the national standard GB / T 2567-2021 (Test Method for Properties of Resin Castings), the relationship between bending strength, bending stress and strain is determined by destroying the specimen at a constant rate or reaching a predetermined deflection value. During the test, the bending strength of substrates such as stainless steel, aluminum, and tempered glass is tested according to the dry adhesion strength method in Section 1.6 of the national standard method, and after the substrate is thermally cured, the bending strength test is performed after the substrate cools to room temperature. The specific method is as follows:
[0147] 1) The adhesive A-LTA prepared according to the method of Example 3 was applied on the surface of a substrate (stainless steel, aluminum, tempered glass) with a size of 120 mm in length and 25 mm in width, with a coating area of 12.5 mm × 25 mm and a thickness of 0.1 mm, and then the two coated substrates were bonded; then placed in a muffle furnace and subjected to heat curing treatment at a curing temperature of 245° C.; after curing treatment for 4 minutes, the substrate was taken out, and after cooling to room temperature, pressure was applied to the coated area to perform a three-point bending strength test;
[0148] The adhesive A-LTA prepared according to the method of Example 3 was heated to 190°C, and maintained at 190°C for 20 minutes (i.e., the adhesive was in a fluid state and not cured after a thermal reaction at 190°C for 20 minutes), and then the adhesive was applied on the surface of a substrate (dragon bamboo, poplar) with a size of 120 mm in length and 25 mm in width, with a coating area of 12.5 mm×25 mm and a thickness of 1 mm; then the two coated substrates were quickly bonded; and then the adhesive was completely cured after being cooled to room temperature, and after the substrate was cooled to room temperature, pressure was applied to the coated area to perform a three-point bending strength test;
[0149] For substrates that are not resistant to high temperatures, such as bamboo, poplar, and paper, which do not require high adhesion strength, the A-LTA adhesive can be heated to a temperature above 67°C and then directly applied to the substrate after the adhesive melts.
[0150] 2) This test case tests the bending strength of adhesive bonding of stainless steel, aluminum, and tempered glass substrates. The three-point bending test was performed using an AGX-V-5KN universal testing machine. The three-point bending program (5000N) was selected, and the compression rate was 10mm.min. -1 The bonding point of the substrate (i.e. the glue coating point) is placed in the center of the test platform, and the downward pressure is continuously applied to the adhesive bonding point until the bonding point of the two substrates breaks. Then the test is stopped and the force conditions are recorded. The parallel test is performed three times. The bending strength calculation formula (1) is as follows:
[0151]
[0152] Where: α is the bending strength, MPa; P is the maximum load, N; L is the span, mm; b is the specimen width, mm; h is the specimen thickness, mm.
[0153] 3) Bending strength test of commercially available adhesives
[0154] Commercially available metal welding glue (product 1), epoxy resin structural glue (product 2) and Shuangyi all-purpose adhesive (product 3) were used as positive control products to test their bending strength of stainless steel substrates. That is, the three commercially available adhesives were applied to a stainless steel substrate with a length of 120 mm and a width of 25 mm, with a coating area of 12.5 mm × 25 mm and a thickness of 1 mm. After coating, the two substrates in the coated area were bonded to each other. After being placed at room temperature for 24 hours, the bending strength of different adhesives was tested.
[0155] The results of the bending test are as follows Fig.12 As shown, A) is a bending strength test diagram of the A-LTA adhesive of the present invention bonded to different substrates; B) is a bending strength test diagram of the A-LTA adhesive and a commercially available adhesive bonded to a stainless steel substrate.
[0156] Depend on Fig.12 A It can be seen that the bending strength of the adhesive A-LTA of the present invention for different substrates such as steel, aluminum, and tempered glass are 139.67, 60.56, and 45.66 MPa, respectively. The strength variation law of the obtained bending strength is basically consistent with the adhesion strength result, that is, stainless steel>aluminum>tempered glass.
[0157] Fig.12 B shows that the flexural strength of adhesive A-LTA is higher than that of all commercially available adhesives, indicating that A-LTA has excellent bonding effect on metal substrates, which may be due to the rich functional groups and highly cross-linked network structure of A-LTA adhesive.
[0158] Test Example 7 Adhesion Strength Test under Different Usage Environments
[0159] Generally speaking, the environment in which adhesives are used is changeable, especially in harsh environments such as seawater, acid, alkali, and organic solvents, where maintaining long-term effective adhesion is a greater challenge.
[0160] Apply glue on one side of two stainless steel substrates, with a length of 12.5 mm, a width of 25 mm, and a thickness of 0.1 mm. After the glue is applied, bond the two stainless steels in the glued area and apply a unit area (mm 2 ) is 1.38MPa, and after applying pressure for 1min, the adhesive stainless steel substrate is obtained and set aside;
[0161] The bonded stainless steel substrates were placed in a muffle furnace for heat curing at a temperature of 245°C. After 4 minutes of heat curing, the substrates were taken out and cooled to room temperature.
[0162] Different adhesive stainless steel substrates after heat curing were placed in 1.0 mol.L -1 HCl solution, 1.0 mol.L -1 Soaking in NaOH solution, 5.0wt% NaCl solution, petroleum ether, and water for 24h and 7 days respectively;
[0163] Take out the soaked stainless steel substrates and measure the adhesive strength according to the national standard GB / T 7124-2008 (Determination of tensile shear strength of adhesives (rigid material to rigid material)). Five specimens are tested in parallel in each group. The adhesive shear strength is tested on a universal testing machine to evaluate the adhesive strength. The fixture spacing is set to 90mm and the test speed is 10mm / min. The test results are as follows: Fig.13 .
[0164] The test results show that compared with the ideal external environment, the bonding strength of the bonded substrates is reduced when they are in different solvent environments. However, the adhesion strength remains above 6.54 MPa regardless of whether they are immersed for 1 day or 7 days. This indicates that the adhesive A-LTA has good underwater bonding stability and therefore has great application potential in various types of environments.
[0165] The present invention prepares a new adhesive A-LTA using shellac terpene acid and melamine as raw materials. The rheological test results show that during the heating process, the viscosity and modulus of A-LTA show a change pattern of first decreasing and then increasing with the increase of temperature. Viscous deformation occurs in the range of 25-225°C, and it mainly exists in the form of a fluid. When the temperature is higher than 225°C, the storage modulus is much greater than the energy dissipation modulus, and a solid substance is generated. The DSC test shows that A-LTA solidifies due to two important chemical cross-linking reactions during the heating process, and the thermogravimetric test shows that the adhesive has good thermal stability. FTIR and XPS characterizations prove that the adhesive A-LTA contains multiple functional groups such as amide, imine, and ester groups. Therefore, A-LTA cross-links and polymerizes under high temperature conditions to form a network structure with multiple chemical bonds and a dense structure. Therefore, the adhesive can have high bonding strength and bending strength on steel, aluminum, tempered glass, dragon bamboo, and poplar. Its performance is better than most commercially available adhesives, showing the potential for general bonding applications on various substrate surfaces. At the same time, the stability test results show that A-LTA can maintain strong and effective bonding effects after being immersed in strong acids, strong alkalis, water and organic solvents for 7 days, and can withstand harsh external environments. It has significant advantages in industrial production and environmental protection, and therefore has great potential for application as a multifunctional adhesive. This paper provides a novel solution and theoretical basis for the high-value utilization of shellac waste liquid, which will help shellac production enterprises adjust their industrial structure and develop a low-carbon development of the green economy.
Claims
1. A method for preparing a shellac terpene acid-based adhesive, characterized in that: The method comprises the steps of cross-linking the shellac terpene acid LTA and a cross-linking agent, wherein the cross-linking agent is melamine, urea, polyethylene glycol, ethylenediamine or triethylenetetramine.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to LTA is (8-23):100, preferably 23:
100.
3. The preparation method according to claim 1 or 2, characterized in that: The cross-linking reaction temperature is 55-85°C, preferably 65-75°C, and more preferably 70°C; the cross-linking reaction time is 0.5-1.5h, and preferably 1h.
4. A method for preparing a shellac terpene acid-based adhesive, characterized in that: The steps include the following steps in order: 1) dissolving shellac terpene acid LTA in sodium hydroxide solution to prepare LTA-sodium hydroxide solution; 2) adding melamine to the LTA-sodium hydroxide solution to carry out a cross-linking reaction; 3) adding formic acid as a pH additive to the cross-linking reaction mixture to adjust the pH of the reaction mixture, and stirring the reaction mixture for at least 30 minutes while maintaining the pH value of the reaction mixture at 3-5; 4) After stirring, the reaction solution is cooled to room temperature and allowed to stand for stratification, the upper clear liquid is discarded, and the lower viscous material is washed with water until it becomes neutral, thereby obtaining a shellac terpene acid-based adhesive.
5. The preparation method according to claim 4, characterized in that: The ratio of the mass of LTA to the volume of the sodium hydroxide solution in step 1) is 1:(1-15) g / ml, preferably 1:10 (g / ml).
6. The preparation method according to claim 4 or 5, characterized in that: In step 2), the mass ratio of melamine to LTA in the LTA-sodium hydroxide solution is (8-23):
100.
7. The preparation method according to claim 4 or 5, characterized in that: The pH adjuster in step 3) is formic acid, acetic acid, or propionic acid, preferably formic acid.
8. A shellac terpene acid-based adhesive, characterized in that: Prepared according to the method as described in any one of claims 1 to 7.
9. An application of the shellac terpene acid-based adhesive as claimed in claim 8, characterized in that: After the shellac terpene acid-based adhesive is applied to the substrate to be bonded, a heat curing treatment is performed, wherein the heat curing treatment temperature is 200-250° C.; The heat curing time is at least 3 minutes; or the shellac terpene acid-based adhesive is heated to >67°C, melted and coated on the substrate to be bonded, and then cooled and bonded into one piece.
10. The use according to claim 9, characterized in that: The heat curing treatment temperature is 200-250° C., preferably 215-250° C., and more preferably 245° C.; the heat curing time is 3-10 min, and preferably 4 min.